Design and implementation of the ground test and verification bed for BeiDou navigation satellite system - GUO Shuren (Acta Geodaetica et Cartographica Sinica, 2020)
The BeiDou Navigation Satellite System (BDS) is a constantly-updated huge system with tightly-coupled space and ground segments and long construction period. Faced with the multiple challenges of highly complicated key technical scheme, high-intensity satellite deployment and launching tasks, and high difficulty in system stable operation, BDS has very high demands for the system's test and verification. This paper analyzes the test and verification tasks of BDS including system design and verification, space and ground segment integration, and simulation operation, and proposes the system architecture of the ground test and verification bed which equivalent to the full-system, full-scale and full-elements BDS. The bed is featured with synchronized work of the software and hardware platforms, equivalent operation of the simulation and real systems, and remote connection between the test bed and system segments, and solves the problems of multi-system simulation modeling, high-dynamic simulation as well as software and hardware synchronized simulation; realizes the whole process verification of the BDS design, deployment and operation, and also realizes the test and verification of the BDS new technical schemes such as inter-satellite links, BDS satellite autonomous integrity monitoring, and precise orbit determination. The bed for BDS is the only test and verification system in the field of satellite navigation that can realize all-states system simulation, and synchronized iterative evolution and operation with the real system, and can serve as important reference for the verification work of other space missions.